2002
DOI: 10.4049/jimmunol.168.3.1190
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Induced Nonresponsiveness: A Th-Dependent Regulatory Checkpoint in the CTL Response

Abstract: CD8 T cells undergo autocrine IL-2-dependent proliferation upon TCR engagement and costimulation, but within 3–4 days, they become activation-induced nonresponsive (AINR) and display a split anergy. They can lyse targets and secrete IFN-γ but they cannot produce IL-2 in response to TCR ligation and costimulation, due at least in part to an inability to up-regulate mitogen-activated protein kinases and IL-2 mRNA. Exogenous IL-2 can drive continued proliferation of AINR cells and nonresponsiveness is reversed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 45 publications
(37 reference statements)
5
60
0
1
Order By: Relevance
“…The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49). We found that cultures of stimulated gal-1-deficient CD8 cells produce more IL-2 than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49). We found that cultures of stimulated gal-1-deficient CD8 cells produce more IL-2 than their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies by Mescher and colleagues (47)(48)(49) have identified a period of activation-induced nonresponsiveness (AINR) in CD8 T cells 2-4 days after initial TCR engagement, wherein CD8 T cells become unable to produce IL-2 or proliferate in response to secondary TCR engagement. The addition of exogenous IL-2 can reverse AINR, which has been characterized to result from impaired TCR-induced MAPK activation (including ERK) and IL-2 production (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests ongoing cytotoxic activity against bone marrow-derived APC expressing the cognate Ag at high levels. In that respect CD8 T cells from NP47F5 mice seem to undergo activation induced nonresponsiveness, which was described as a part of the differentiation program of CD8 T cells (38). However, in contrast to T cells undergoing activation induced nonresponsiveness they do not secrete IFN-␥.…”
Section: Discussionmentioning
confidence: 98%
“…Activated CD4 T cells are the major producers of IL-2, a cytokine important to CD8 T cells for the relief of split anergy (10,11), the maintenance of effector populations (12,13), and the promotion of antitumor immunity (14,15). Although the effects of IL-2 on CD8 T cells are diverse, they are limited to the promotion of proliferation and/or survival and do not include the induction of de novo effector functions.…”
Section: Il-21 Promotes Differentiation Of Naive Cd8 T Cells To a Unimentioning
confidence: 99%